Development of a rapid and simple voltammetric method to determine total antioxidative capacity of edible oils - Gulaboski, Rubin; Mirčeski, Valentin; Mitrev, Saša (Elsevier BV, 2013)
In this work we report on a new, rapid and simple voltammetric method to determine the total antioxidant capacity (TAC) of the edible oils. The method explores the ABTS radical (2,2'-azinobis(3-ethylbenzothiazoline-6-sulphonic acid)) assay as a redox probe and it relays on measuring catalytic voltammetric currents. The electrocatalysis comprises redox regeneration of the electrochemically created ABTS(+) radical either by Trolox (6-hydroxy-2,5,7,8-tetramethychroman-2-carboxylic acid) or by antioxidants present in studied oils. The detection limit of the method is determined to be 0.5 mg/L of Trolox equivalent, being a slightly lower than the corresponding UV-VIS spectrophotometric method. Applying the proposed voltammetric method the total antioxidant capacity of three types of commercially available cold-pressed edible oils are determined, and the results are found to be in a very good agreement with those obtained by UV-VIS spectrophotometry. The reported voltammetric method is cheap, rapid and simple, and it can be used as a sustainable alternative to the UV-VIS methods for the determination of total antioxidant capacitance of oils and other liquid lipophilic nutrients. Potent antioxidant capacity of studied oils was also confirmed by electron paramagnetic resonance spectroscopy of superoxide anion produced by macrophages.